HUBUNGAN POSISI KERJA DENGAN MUSKULOSKELETAL DISORDER PADA PEKERJA SANDAL HARLES KOTA MOJOKERTO - Emi Yuliarahman; Mahmudah, Rifaatul Laila (MEDICA MAJAPAHIT, 2022)
Work positions that are not ergonomic in the informal sector can lead to musculoskeletal disorders. Musculoskeletal disorders are health problems that occur in jobs that often use muscle strength and work positions that are not ergonomic. This study aims to determine the relationship between work position and musculoskeletal disorders in Harles sandal workers in Mojokerto.This research is descriptive research with cross sectional design. The population in the study was 57 people with a sample of 37 people taken using cluster random sampling. The instrument used to measure work position was the REBA questionnaire and measuring musculoskeletal disorders with the NBM questionnaire.The results showed that most of the work positions were moderate risk as many as 33 respondents (70.3%) and musculoskeletal disorder as many as 20 people (54.1%) who had a high risk category. Data analysis used Spearman Rho Test with significant results of 0.438 so that it can be concluded that p 0.007 <0.05, which means that there is a relationship between work position and musculoskeletal disorder in harles sandal workers in Mojokerto City.Efforts that can be made to reduce musculoskeletal disorders include stretching the muscles a few minutes before and after work to relax muscle tension.